Sustainable Development A Challenge for the World Economy - Torsten Amelung (Conversion - Opportunities for Development and Environment, 1992)
Most economies in the world have been on a track that was based on an irreversible consumption of natural resources in order to fuel their economic growth. For developing nations, this process has just started. In order to help developing nation to leap-frog into a strategy that is less wasteful with respect to the consumption of the natural resources, it would make snse to set up an international transfer system that pays developing nations for the positive global external effects caused by their sustainable development policies.
Keywords: F64; Q01; Q56; 330